A comparative analysis of the efficacy of moxifloxacin and cefixime in the reduction of postoperative inflammatory sequelae after mandibular third molar surgery - Stošić, Branimir; Šarčev, Ivan; Mirković, Siniša; Bajkin, Branislav; Soldatović, Ivan (Vojnosanitetski pregled, 2022)
Background/Aim. There is no scientific evidence that the prophylactic use of antibiotics as a part of the mandibular third molar surgery is effective in suppressing postoperative pain, edema, trismus, and dry socket. The aim of the study was to investigate the effects of antibiotics from the fluoroquinolone (moxifloxacin) and cephalosporin (cefixime) groups in reducing postoperative inflammatory sequelae (pain, edema, and trismus), as well as in possibly reducing the incidence of dry socket after mandibular third molar surgery. Methods. This double-blind study was completed by 157 subjects, comprising two study groups (who received the aforementioned antibiotics) and a control group, who received placebo tablets. Subjects were assessed on the first, second, and seventh day following surgery. In the postoperative course, patients were monitored for the occurrence, intensity, and duration of postoperative inflammatory sequelae and dry socket. Results. Both antibiotics, especially moxifloxacin, had a pronounced effect on reducing all inflammatory sequelae (pain, edema, and trismus) as the most common postoperative complaints following mandibular third molar surgery, and also contributed to reducing the incidence of dry socket. Conclusion. Antibiotic prophylaxis with cefixime and, especially moxifloxacin, reduced the occurrence of postoperative inflammatory sequelae and alleviated discomfort. It is interesting, that both antibiotics, especially moxifloxacin, also contributed to reducing the incidence of postoperative dry socket, which is not provoked by inflammation. Therefore, further research into the underlying mechanisms behind such an effect is warranted.
Keywords: anti-bacterial agents; dental prophylaxis; molar, third; postoperative complications.